Catalyst nanoparticle growth dynamics and their influence on product morphology in a CVD process for continuous carbon nanotube synthesis. (January 2016) - Hoecker, Christian; Smail, Fiona; Bajada, Mark; Pick, Martin; Boies, Adam
Abstract: Extrapolating the properties of individual CNTs into macro-scale CNT materials using a continuous and cost effective process offers enormous potential for a variety of applications. The floating catalyst chemical vapor deposition (FCCVD) method discussed in this paper bridges the gap between generating nano- and macro-scale CNT material and has already been adopted by industry for exploitation. A deep understanding of the phenomena occurring within the FCCVD reactor is thereby key to producing the desired CNT product and successfully scaling up the process further. This paper correlates information on decomposition of reactants, axial catalyst nanoparticle dynamics and the morphology of the resultant CNTs and shows how these are strongly related to the temperature and chemical availability within the reactor. For the first time, in-situ measurements of catalyst particle size distributions coupled with reactant decomposition profiles and a detailed axial SEM study of formed CNT materials reveal specific domains that have important implications for scale-up. A novel observation is the formation, disappearance and reformation of catalyst nanoparticles along the reactor axis, caused by their evaporation and re-condensation and mapping of different CNT morphologies as a result of this process.